PENCIPTAAN PEREMPUAN: ANTARA MITOS DAN FAKTA - Musolli Musolli (JURNAL AT-TURAS, 2016)
The patriarchial system has been considerable in the socio-cultural construction of the parts of world, as it legitimated a fact that male is conceived as having a higher position than female. The existence of religion argues that a theological interpretation is still based on gender bias. The creation of female from male’s rib bone as a result of interpretation to the nafsin wâhidah is basically designed in terms of isrâiliyyât  over the story. By examining many interpretatory books, this article is to argue that nafsin wâhidah in Quran told equality between male and female, not a biological creation of female.